Density‐dependence and seasonal variation in reproductive output and sporophyte production in the kelp, Ecklonia radiata. Issue 1 (17th November 2021) - Tatsumi, Masayuki; Mabin, Christopher J. T.; Layton, Cayne; Shelamoff, Victor; Cameron, Matthew J.; Johnson, Craig R.; Wright, Jeffrey T.
Abstract : The kelp, Ecklonia radiata, is an abundant subtidal ecosystem engineer in southern Australia. Density‐dependent changes in the abiotic environment engineered by Ecklonia may feedback to affect reproduction and subsequent recruitment. Here, we examined: 1) how the reproductive capacity of Ecklonia individuals in the field (zoospores released · mm −2 reproductive tissue) varied with adult density and time,  and 2) how the recruitment of microscopic gametophytes and sporophytes was influenced by zoospore density at two times. Zoospore production did not vary with adult density, with only one month out of ten sampled over a 2‐y period showing a significant effect of density. However, zoospore production varied hugely over time, being generally highest in mid‐autumn and lowest in mid‐late summer. There were strong effects of initial zoospore density on gametophyte and sporophyte recruitment with both a minimum and an optimum zoospore density for sporophyte recruitment, but these varied in time. Almost no sporophytes developed when initial zoospore density was <6.5 · mm −2 in spring or <0.5 · mm −2 in winter with optimum densities of 90‐355 · mm −2 in spring and 21‐261 · mm −2 in winter, which resulted in relatively high recruitment of 4‐7 sporophytes · mm −2 . Sporophyte recruitment declined at initial zoospore densities >335 · mm −2 in spring and >261 · mm −2 in winter and was zero at very high zoospore densities. These findings suggest that although adult Ecklonia density does not affect per‐capita zoospore production, because there is a minimum zoospore density for sporophyte production, a decline in population‐level output could feedback to impact recruitment.